Antifungal, Cytotoxic, and Immunomodulatory Properties of Tea Tree Oil and Its Derivative Components: Potential Role in Management of Oral Candidosis in Cancer Patients - Ramage, Gordon; Milligan, Steven; Lappin, David F.; Sherry, Leighann; Sweeney, Petrina; Williams, Craig; Bagg, Jeremy; Culshaw, Shauna (Frontiers in Microbiology, 2012)
Candida albicans forms oral biofilms that cause disease and are difficult to treat with conventional antifungal agents. Tea tree oil (TTO) is a natural compound with reported antimicrobial and immunomodulatory activities. The aims of the study were to evaluate the antifungal efficacy of TTO and key derivatives against C. albicans biofilms, to assess the toxicological effects of TTO on a clinically relevant oral cell line, and to investigate its impact on inflammation. TTO and its derivatives were examined against 100 clinical strains of C. albicans. Planktonic minimum inhibitory concentrations (MICs) were determined using the CLSI M-27A broth microdilution method. Sessile MICs were determined using an XTT reduction assay. Inhibition, time-kill and mode of action studies were performed. OKF6-TERT2 epithelial cells were used for cytotoxicity and cytokine expression assays. Planktonic C. albicans isolates were susceptible to TTO, terpinen-4-ol (T-4-ol) and α-terpineol, with an MIC50 of 0.5, 0.25 and 0.25%, respectively. These three compounds also displayed potent activity against the 69 biofilm-forming strains, of which T-4-ol and α-terpineol displayed rapid kill kinetics. For all three compounds, 1 × MIC50 effectively inhibited biofilm growth when C. albicans were treated at 0, 1 and 2 h post adhesion. By SEM analysis and PI uptake, TTO and derivative components were cell membrane active. TTO and T-4-ol were cytotoxic at 1 × MIC50, whereas at 0.5 × MIC50 T-4-ol displayed no significant toxicity. Transcript and protein analysis showed a reduction of IL-8 when treated with TTO and T-4-ol. These data provide further in vitro evidence that TTO and its derivative components, specifically T-4-ol, exhibit strong antimicrobial properties against fungal biofilms. T-4-ol has safety advantages over the complete essential oil and may be suitable for prophylaxis and treatment of established oropharyngeal candidosis. A clinical trial of T-4-ol is worthy of consideration.